Cross‐sectional and prospective associations of sleep duration and bedtimes with adiposity and obesity risk in 15 810 youth from 11 international cohorts. Issue 4 (1st December 2021) - Collings, Paul J.; Grøntved, Anders; Jago, Russell; Kriemler, Susi; Northstone, Kate; Puder, Jardena J.; Salmon, Jo; Sardinha, Luís B.; Steene‐Johannessen, Jostein; van Sluijs, Esther M. F.; Sherar, Lauren B.; Esliger, Dale W.; et al.
Summary: Objectives: To investigate associations of bedtimes and sleep durations with adiposity levels in children and adolescents. Methods: Individual data were pooled for 12 247 children (5819 with follow‐up adiposity at 2.3 ± 1.4 years post‐baseline) and 3563 adolescents from 11 international studies. Associations between questionnaire‐based sleep durations, bedtimes and four groups of combined bedtimes and sleep lengths (later‐shorter [reference]/earlier‐shorter/later‐longer/earlier‐longer) with measured adiposity (body mass index [BMI] and waist circumference z ‐scores) and weight status, were investigated. Results: In children, longer sleep durations were consistently associated with lower adiposity markers, and earlier bedtimes were related to lower BMI z ‐score. Compared to sleeping <10 h, longer baseline sleep duration favourably predicted Δwaist z ‐score in girls (≥10 and <11 h (β‐coefficient (95% confidence interval [CI])): −0.06 (−0.12 to −0.01)) and boys (≥11 h: −0.10 [−0.18 to −0.01]). Combined groups that were defined by longer sleep (later‐longer and earlier‐longer sleep patterns) were associated with lower adiposity, and later‐longer sleep favourably predicted Δwaist z ‐score in girls (−0.09 [−0.15 to −0.02]). In adolescents, longer sleep durations and earlier bedtimes were associated with lower BMI z ‐score in the whole sample, and also with lower waist z ‐score in boys. Combined groups that were characterized by earlier bedtimes were associated with the same outcomes. For example, earlier‐shorter (−0.22 (−0.43 to −0.01) and earlier‐longer (−0.16 (−0.25 to −0.06) sleep were both associated with lower BMI z ‐score. Conclusions: If the associations are causal, longer sleep duration and earlier bedtimes should be targeted for obesity prevention, emphasizing longer sleep for children and earlier bedtimes for adolescents.